Vibrational Spectroscopy Investigation Using Ab Initio and Density Functional Theory Analysis on the Structure of tert-Butyl 3a-Chloroperhydro-2,6a-epoxyoxireno[e]isoindole-5-carboxylate - Hakan Arslan; Aydin Demircan; Gun Binzet; Ilhan Ozer Ilhan (Journal of Chemistry)
The molecular structure, vibrational frequencies, and infrared intensities of the tert-butyl 3a-chloroperhydro-2,6a-epoxyoxireno[e]isoindole-5-carboxylate were calculated by the HF and DFT (BLYP and B3LYP) methods using 6-31G(d) and 6-31G(d,p) basis sets. The FT infrared spectrum of the solid sample was measured under standard condition. We obtained two stable conformers for the title compound; however Conformer 1 is approximately 0.2 kcal/mol more stable than the Conformer 2. The comparison of the theoretical and experimental geometry of the title compound shows that the X-ray parameters fairly well reproduce the geometry of Conformer 2. Comparison of the observed fundamental vibrational frequencies of the title molecule and calculated results by HF and DFT methods indicates that B3LYP is superior for molecular vibrational problems. The harmonic vibrations computed by the B3LYP/6-31G(d,p) method are in a good agreement with the observed IR spectral data. Theoretical vibrational spectra of the title compound were interpreted by means of potential energy distributions (PEDs) using VEDA 4 program.